Pengaruh Roe, Eps, Dan Per Terhadap Return Saham Pada Perusahaan Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia - Hartawan, Gita; Manda, Gusganda Suria (Jurnal Ilmiah Wahana Pendidikan, 2026)
Indonesia is ranked 72nd out of 141 countries in terms of infrastructure development, reflecting a notable weakness in the nation’s infrastructure sector. This condition may have implications for the stock returns of companies operating within the sector. This study aims to examine the influence of Return on Equity (ROE), Earnings per Share (EPS), and Price to Earnings Ratio (PER) on stock returns. A multiple linear regression analysis was employed, using a sample of 47 infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2023. The research utilized secondary data obtained from the companies’ financial statements. The sampling method applied was purposive sampling, based on specific selection criteria. The findings indicate that, partially, ROE has a positive and significant effect on stock returns, whereas EPS and PER show negative but insignificant effects. Furthermore, when tested simultaneously, the independent variables collectively have a significant influence on stock returns.